Analisis Kesalahan Fonetis Bacaan Qur’an: Studi Kasus Peserta Tahsin RTQ Maisuuro - Maknun, Lu'luil; Zakaria, Muhammad Fadhlurrahman (Journal of Arabic Language Studies and Teaching, 2025)
This study aims to critically examine the forms of mispronunciation of Qur’anic letters from the aspects of makhārij al-ḥurūf (points of articulation) and ṣifāt al-ḥurūf (characteristics of the letters). It also explores in greater depth the factors that cause these problems to occur, as well as the solutions applied to minimize mistakes in Qur’an recitation. The method employed is a descriptive qualitative method based on a phonological approach with a focus on articulatory phonology. The data source of this study is the Qur’an recitations of participants in the tahsin Qur’an study circle (ḥalaqah) at Rumah Tartil Qur’an Maisuuro. The findings show that the majority of participants frequently make errors in pronouncing isti‘lā’ letters (emphatic letters), such as qāf (ق), ṣād (ص), and others. Occasionally, they also mispronounce light letters, such as ‘ain (ع), rā’ (ر), and so on. Other common phonological mistakes include lengthening or shortening sounds incorrectly, substituting letters or vowels, adding or omitting letters, and similar errors. These mispronunciations are influenced by factors related to the learners themselves, their parents, and their teachers. Therefore, all close stakeholders must be actively involved in the Qur’an learning process at RTQ Maisuuro in order to produce both quality and quantity in Qur’an recitation.